2018
DOI: 10.1007/s00701-018-3676-8
|View full text |Cite
|
Sign up to set email alerts
|

Filling the gap between the OR and virtual simulation: a European study on a basic neurosurgical procedure

Abstract: Background Currently available simulators are supposed to allow young neurosurgeons to hone their technical skills in a safe environment, without causing any unnecessary harm to their patients caused by their inexperience. For this training method to be largely accepted in neurosurgery, it is necessary to prove simulation efficacy by means of large-scale clinical validation studies. Methods We correlated and analysed the performance at a simulator and the actual operative skills of different neurosurgeons (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Advances in augmented reality (AR) have enabled the investigation of digital superimposition of radiographic images onto the surgical field using wireless glasses that do not require a physical footprint in the OR. [3][4][5][6][7] This allows for FIN during neurosurgical cases in a potentially less cumbersome fashion than with MWBNS (Video 1). VIDEO 1.…”
mentioning
confidence: 99%
“…Advances in augmented reality (AR) have enabled the investigation of digital superimposition of radiographic images onto the surgical field using wireless glasses that do not require a physical footprint in the OR. [3][4][5][6][7] This allows for FIN during neurosurgical cases in a potentially less cumbersome fashion than with MWBNS (Video 1). VIDEO 1.…”
mentioning
confidence: 99%
“…This course employed a low tutor to delegate ratio and received excellent feedback on the small group learning with immediate feedback model similar to that of our workshop [28]. Conversely, another VR simulator study confirmed that simulator performance reflects surgeons' ability to place an EVD correctly [30]. Examples of physical simulator models other than ROWENA include MARTYN [23], babyMARTYN [8], Sinus Model Oto-Rhino Neuro Trainer (SIMONT) [11] and the OMeR model (for simulation of deep microvascular anastomosis procedures) [17].…”
Section: Discussionmentioning
confidence: 88%
“…The ImmersiveTouch, a VR simulator, was validated for EVD placement in a multicentre study involving 92 participants 26 . The simulator achieved a rating of 2 for both content and relations to other variables, however only achieved a LoE of 1.…”
Section: Ventriculostomymentioning
confidence: 99%